1993
DOI: 10.1073/pnas.90.8.3373
|View full text |Cite
|
Sign up to set email alerts
|

The role of "indirect" recognition in initiating rejection of skin grafts from major histocompatibility complex class II-deficient mice.

Abstract: In vitro studies have revealed several pathways by which T cells can respond to alloantigens, including CD4+ direct responses to allogeneic class 11 antigens, CD8+ direct responses to allogeneic class I antigens, and CD4+ "indirect" responses to peptides of alloantigens presented in association with responder class 11 molecules. In vivo studies of skin graft rejection, however, have so far provided dear evidence for the contribution of only the two direct pathways and not for indirect recognition. We have used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
161
1
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(174 citation statements)
references
References 40 publications
10
161
1
2
Order By: Relevance
“…These studies, along with others using MHC class I (CI)-and class II (CII)-deficient donors (11), suggested that indirect antigen presentation is an important pathway mediating MHC CI-and MHC CII-disparate allograft rejection. Additionally, experiments using donor-derived peptides to stimulate alloreactive T cells and donor tissues derived from MHC-deficient mice confirmed indirect antigen presentation as an important mechanism in the rejection of allogeneic organs and tissues (4,5,9,(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…These studies, along with others using MHC class I (CI)-and class II (CII)-deficient donors (11), suggested that indirect antigen presentation is an important pathway mediating MHC CI-and MHC CII-disparate allograft rejection. Additionally, experiments using donor-derived peptides to stimulate alloreactive T cells and donor tissues derived from MHC-deficient mice confirmed indirect antigen presentation as an important mechanism in the rejection of allogeneic organs and tissues (4,5,9,(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 94%
“…The direct antigen presentation pathway is sufficient for the rejection of allogeneic skin Previous studies using MHC CII-/-allogeneic donor skin showed that the indirect antigen presentation pathway to CD4π T cells was sufficient to mediate skin allograft rejection (11). To address whether the direct pathway of CD4π T-cell allorecognition can mediate graft rejection, B6 aBM12 TCR Tg mice were grafted with allogeneic BM12 and syngeneic Direct Class II Antigen Presentation and Tolerance B6 skin.…”
Section: B6 Abm12 Tcr Tg T Cells Respond To Bm12 Alloantigen In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have reaffirmed that MHC class I plays a dominant role in skin graft rejection. 62,63 Soluble MHC class I shed by the donor keratinocytes are taken up by recipient's APC and presented to CD4 T cells. The CD4 T cells primed via the indirect pathway of allorecognition mediate inflammatory effects (DTH) as well as activate CD8 CTL that recognize donor MHC class I via the direct pathway.…”
Section: Discussionmentioning
confidence: 99%
“…25,62,[64][65][66][67] However, ␤2-microglobulin and TAP single/double knockout mice still express residual amounts of the MHCI heavy chain that reach the cell surface and are sufficient to trigger a CTL response. [68][69][70] These data suggest that an almost complete MHC class I knockout phenotype is necessary to prevent CTL triggering and action.…”
Section: Discussionmentioning
confidence: 99%